Photon-number statistics of twin beams: Self-consistent measurement, reconstruction, and properties - Jan, Peřina Jr; Haderka Ondřej; Michálek Václav (AIP conference proceedings, 2014)
A method for the determination of photon-number statistics of twin beams using the joint signal-idler photocount statistics obtained by an iCCD camera is described. It also provides absolute quantum detection efficiency of the camera. Using the measured photocount statistics, quasi-distributions of integrated intensities are obtained. They attain negative values occurring in characteristic strips an a consequence of pairing of photons in twin beams.